Immediate and long-term efficacy of executive functions cognitive training in older adults: A systematic review and meta-analysis - Nguyen, Lan; Murphy, Karen; Andrews, Glenda (Psychological bulletin, 2019)
There has been growing interest in enhancing cognition in older adulthood via computerized cognitive training (CCT), though, there is controversy surrounding the efficacy of CCT in promoting improvements to functional everyday activities. As core executive-functions (EFs)-cognitive-flexibility, inhibition, working memory-are applicable to most aspects of daily living, CCT targeting these processes would likely promote gains on trained tasks, and potentially on similar untrained tasks (near-transfer), and general cognitive performance (far-transfer). We report two meta-analyses investigating the immediate (pretest to posttest) and long-term efficacy (pretest to follow-up) of core-EF CCT in improving cognition among older adults. Sixty-four studies (encompassing 3,594 participants) included an eligible CCT intervention targeting at least 1 core-EF (e.g., working memory training). Both immediate and long-term efficacy analyses revealed significant, large training effects for trained outcomes, and significant, small training effects for near-transfer and far-transfer outcomes. When comparing the same studies, effect sizes from immediate and long-term efficacy analyses were comparable, suggesting that CCT gains were maintained over time. Further analyses of immediate efficacy revealed significant, small training effects for performance on executive functioning, fluid intelligence, memory, and visuospatial domains, but not for attention or processing speed. After adjusting for publication bias, the training effect for fluid intelligence was nonsignificant, whereas processing speed was significant. It is recommended that future studies employ adaptive multidomain training as these studies were shown to produce significant training effects at each transfer level. Overall, core-EF CCT interventions show promise in promoting immediate and long-term improvements in cognitive performance among older adults. (PsycINFO Database Record (c) 2019 APA, all rights reserved).